(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyses a big votive offering which is located on the high choir of Santa Catalina de Sienna church in Morelia, better known as “Las Monjas” (The Nuns). The painting shows the nuns’ daily life and the activities they were performing when a spark got into the choir window without hurting them. To analyze the painting the social and religious context have been taken into consideration so that people can access that time way of thinking. An iconographic analysis has also been made to identify the different elements that the painting has and their meaning. A formal study has been made in order to learn the technical aspects of the painting which shows the composition, the lightening, the rhythm, the color and the skilled used of the brush. The votive offering is related to the Dormicion Virgin devotion.